MEMBANGUN WEB FILTERING DENGAN DNS FORWARDING PADA JARINGAN WIRELESS BERBASIS MIKROTIK PADA SMANEGERI 1 PALOPO - Munira Munira; Dasril Dasril; Hisma Abduh (CV. Denasya Smart Publisher, 2024)
Internet use in educational environments requires strict supervision to control web access to ensure compliance with school policies and safe use for students and teaching staff. This research aims to develop a web filtering solution using Dns forwarding jaringan wirelesstechnology on a Mikrotik-based wireless network at SMA Negeri 1 Palopo. The research method used is experimental with a quantitative approach. Data was collected through observation, interviews and literature study. Next, the Dns forwarding jaringan wirelessconfiguration is implemented on the Mikrotik device to implement web access control based on predetermined content categories. The research results show that the use of Dns forwarding jaringan wirelesson Mikrotik-based wireless networks is able to provide effective control over web access. Network administration can easily set access restrictions based on content categories, such as social media, gambling, and other dangerous sites. This solution is expected to increase monitoring efficiency and provide a safer and more productive internet environment at SMA Negeri 1 Palopo.